Efforts to Facilitate the Community in Religious Activities by Forming a Mosque Youth Association in RW 01 Dusun 2 Mekarsari Village - Gina Khoirunnisa; Hanifah El Khairiah; Wahid Saepul; Muhammad Al Mighwar (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2025)
Mekarsari Village is a village located in Cimaung District, Bandung Regency which is also a place for KKN group 164 of UIN Sunan Gunung Djati Bandung with the theme Community Empowerment Systems and Religious Moderation. Group 164 has a post in Hamlet 2 RW 01 or Mekarsari village, right where the Mekarsari Village Office is located. Kp. Mekarsari is a village that has been affected by modernization so that the majority of the village community has little concern for religion, both in terms of education and activities, with the theme of a system of community empowerment and religious moderation, facilities are needed that can increase community awareness of these two things, namely the existence of youth ties. mosque. The aim of this activity is to increase awareness and interest in learning from the community, both children and adults, so that religious education and religious activities can be carried out and their existence is maintained in the area. The research methods used were observation, interviews, literature study and documentation. The results of the research show that with the existence of mosque youth ties, religious education and religious activities can be carried out well so that people care more about religion.